Fenretinide derivatives act as disrupters of serum Retinol Binding Protein (sRBP) interactions with Transthyretin (TTR) and the sRBP Receptor - Campos-Sandoval, José Ángel; Redondo, Clara; Kinsella, Gemma; Akos, Pal; Geraint, Jones; Eyre, Gwen; Hirst, Simon; Findlay, John (ACS Publications, 2011)
Serum retinol binding protein (sRBP) is released from the liver as a complex with transthyretin (TTR), a process under the control of dietary retinol. Elevated levels of sRBP may be involved in reducing cellular responses to insulin and in generating, first insulin resistance, then type 2 diabetes, offering a new target for therapeutic attack for these conditions. A series of retinoid analogues were synthesised and examined for their binding to sRBP and their ability to disrupt the sRBP-TTR and sRBP-sRBP receptor interactions. A number inhibit the sRBP-TTR and sRBP-receptor interactions similar to or better than Fenretinide (FEN), presenting a potential novel dual mechanism of action and perhaps offering a new therapeutic intervention against type 2 diabetes and its development. Shortening the chain length of the FEN derivative substantially abolished binding to sRBP, indicating that the strength of the interaction lies in the polyene chain region. Differences in potency against the sRBP-TTR and sRBP-receptor interactions suggest variant effects of the compounds on the two loops of sRBP guarding the entrance of the binding pocket which are responsible for these two protein-protein interactions.
Keywords: Vitamina A; Retinol; Retinol-binding protein; Fenretinide; Insulin resistance; Type 2 diabetes; Transthyretin; Retinoids; TR-FRET; SPR; sRBP receptor